Multimodal-Driven Emotion-Controlled Facial Animation Generation Model - Qiu, Zhenyu; Luo, Yuting; Zhou, Yiren; Gao, Teng (EAI Endorsed Transactions on Scalable Information Systems, 2025)
INTRODUCTION: In recent years, the generation of facial animation technology has emerged as a prominent area of focus within computer vision, achieving varying degrees of progress in lip-synchronization quality and emotion control. OBJECTIVES: However, existing research often compromises lip movements during facial expression generation, thereby diminishing lip synchronisation accuracy. This study proposes a multimodal, emotion-controlled facial animation generation model to address this challenge. METHODS: The proposed model comprises two custom deep-learning networks arranged sequentially. By inputting an expressionless target portrait image, the model generates high-quality, lip-synchronized, and emotion-controlled facial videos driven by three modalities: audio, text, and emotional portrait images. RESULTS: In this framework, text features serve a critical supplementary function in predicting lip movements from audio input, thereby enhancing lip-synchronization quality. CONCLUSION: Experimental findings indicate that the proposed model achieves a reduction in lip feature coordinate distance (L-LD) of 5.93% and 33.52% compared to established facial animation generation methods, such as MakeItTalk and the Emotion-Aware Motion Model (EAMM), and a decrease in facial feature coordinate distance (F-LD) of 7.00% and 8.79%. These results substantiate the efficacy of the proposed model in generating high-quality, lip-synchronized, and emotion-controlled facial animations.